Developing a framework of core competencies in implementation research for low/middle-income countries - Alonge, Olakunle; Rao, Aditi; Kalbarczyk, Anna; Maher, Dermot; Gonzalez Marulanda, Edwin Rolando; Sarker, Malabika; Ibisomi, Latifat; Dako-Gyeke, Phyllis; Mahendradhata, Yodi; Launois, Pascal; Vahedi, Mahnaz (BMJ Journals, 2022)
This article was published in BMJ Global Health [ © Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ] and the definite version is available at: http://dx.doi.org/10.1136/bmjgh-2019-001747. The Journal's website is at: https://gh.bmj.com/content/4/5/e001747